Citrate and malonate increase microbial activity and alter microbial community composition in uncontaminated and diesel-contaminated soil microcosms - B. C. Martin (SOIL, 2016)
Petroleum hydrocarbons (PHCs) are among the most prevalent sources of environmental contamination. It has been hypothesized that plant root exudation of low molecular weight organic acid anions (carboxylates) may aid degradation of PHCs by stimulating heterotrophic microbial activity. To test their potential implication for bioremediation, we applied two commonly exuded carboxylates (citrate and malonate) to uncontaminated and diesel-contaminated microcosms (10 000 mg kg−1; aged 40 days) and determined their impact on the microbial community and PHC degradation. Every 48 h for 18 days, soil received 5 µmol g−1 of (i) citrate, (ii) malonate, (iii) citrate + malonate or (iv) water. Microbial activity was measured daily as the flux of CO2. After 18 days, changes in the microbial community were assessed by a community-level physiological profile (CLPP) and 16S rRNA bacterial community profiles determined by denaturing gradient gel electrophoresis (DGGE). Saturated PHCs remaining in the soil were assessed by gas chromatography–mass spectrometry (GC-MS). Cumulative soil respiration increased 4- to 6-fold with the addition of carboxylates, while diesel contamination resulted in a small, but similar, increase across all carboxylate treatments. The addition of carboxylates resulted in distinct changes to the microbial community in both contaminated and uncontaminated soils but only a small increase in the biodegradation of saturated PHCs as measured by the n-C17 : pristane biomarker. We conclude that while the addition of citrate and malonate had little direct effect on the biodegradation of saturated hydrocarbons present in diesel, their effect on the microbial community leads us to suggest further studies using a variety of soils and organic acids, and linked to in situ studies of plants, to investigate the role of carboxylates in microbial community dynamics.